Is Rationing in the Microfinance Sector Determined by the Microfinance Type? Evidence from Ghana - Luis Diaz-Serrano; Frank Gyimah Sackey (Institute for the Study of Labor (IZA), 2015)
This study sets out to examine the extent to which access to credit and credit rationing are influenced by the microfinance type based on the major factors determining micro, small and medium enterprises' access to credit from microfinance institutions in the era of financial liberalization. The data for the study were gleaned from fourteen microfinance institutions' credit and loan records consisting of borrowers and credit characteristics. Our results are puzzling and show that credit rationing is not influenced by the microfinance types but by the individual microfinance institutions.
Keywords: G21; 330; microfinance; Ghana; credit rationing